2004
DOI: 10.2174/1389450043345443
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeting of Drug Delivery Systems to Cancer

Abstract: This review presents molecular targeting approaches in anticancer drug delivery systems (DDS) and identifies new developments in these systems. Targeting approaches include passive targeting (enhanced permeability and retention effect), targeting specific tumor conditions, topical delivery and active targeting, namely, targeting organs, cells, intracellular organelles and molecules, sandwich targeting, promoter targeting, indirect targeting and targeting by external stimuli. A novel advanced proapoptotic antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 0 publications
3
116
0
Order By: Relevance
“…LHRH peptide is a ligand for the receptors that are overexpressed in plasma membrane of breast, ovarian, and prostate cancer cells [26,29,37] and, as found in the present study, in some types of lung cancer cells. In contrast, the expression of these receptors in healthy organs in most cases is non-detectable [23,38].…”
Section: Discussionsupporting
confidence: 82%
“…LHRH peptide is a ligand for the receptors that are overexpressed in plasma membrane of breast, ovarian, and prostate cancer cells [26,29,37] and, as found in the present study, in some types of lung cancer cells. In contrast, the expression of these receptors in healthy organs in most cases is non-detectable [23,38].…”
Section: Discussionsupporting
confidence: 82%
“…Overexpression of the luteinizing hormone-releasing hormone (LHRH) receptor has been reported in breast, ovarian, and prostate cancer cells, [16][17][18][19] whereas no detectable expression of LHRH receptors has been observed in most visceral organs. Previous reports by Dharap et al 17,20 and Tang et al 19 demonstrated that LHRH peptide could be used as a targeting moiety on drug-delivery systems to enhance drug uptake by breast, ovarian, and prostate cancer cells, and reduce the relative availability of the toxic drug to normal cells.…”
Section: Liu Et Almentioning
confidence: 99%
“…Tumor targeting of a cytotoxic agent refers to the passive accumulation of nano-scaled drug carriers to solid tumors, followed by active internalization into tumor cells [1]. The internalization of drug, either alone or along with a carrier, is required for cell death because most cytotoxic drugs act intracellularly [2,3].…”
Section: Introductionmentioning
confidence: 99%